Posterior Transpedicular Dynamic Stabilization versus Total Disc Replacement in the Treatment of Lumbar Painful Degenerative Disc Disease: A Comparison of Clinical Results - Tunc Oktenoglu; Ali Fahir Ozer; Mehdi Sasani; Yaprak Ataker; Cengiz Gomleksiz; Irfan Celebi (Advances in Orthopedics)
Study Design. Prospective clinical study. Objective. This study compares the clinical results of anterior lumbar total disc replacement and posterior transpedicular dynamic stabilization in the treatment of degenerative disc disease. Summary and Background Data. Over the last two decades, both techniques have emerged as alternative treatment options to fusion surgery. Methods. This study was conducted between 2004 and 2010 with a total of 50 patients (25 in each group). The mean age of the patients in total disc prosthesis group was 37,32 years. The mean age of the patients in posterior dynamic transpedicular stabilization was 43,08. Clinical (VAS and Oswestry) and radiological evaluations (lumbar lordosis and segmental lordosis angles) of the patients were carried out prior to the operation and 3, 12, and 24 months after the operation. We compared the average duration of surgery, blood loss during the surgery and the length of hospital stay of both groups. Results. Both techniques offered significant improvements in clinical parameters. There was no significant change in radiologic evaluations after the surgery for both techniques. Conclusion. Both dynamic systems provided spine stability. However, the posterior dynamic system had a slight advantage over anterior disc prosthesis because of its convenient application and fewer possible complications.